2018
DOI: 10.3389/fonc.2018.00501
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Knowledge, Perception, and Risk Awareness About Breast Cancer and Its Treatment Outcome Among University of Gondar Students, Northwest Ethiopia

Abstract: Background: Breast cancer is among the most common life-threatening public health problems of global concern including Ethiopia. Knowledge and awareness about the disease will help to reduce the number of cases who present at late stages of the disease. The objective of this survey was to assess the knowledge, perception and risk awareness about breast cancer among female medical and health science students of University of Gondar, Ethiopia.Methods: A cross sectional survey was conducted from May 03 to June 01… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
29
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 17 publications
8
29
3
Order By: Relevance
“…The data showed that our students agreed that breastfeeding does not affect the incidence of BC. Similar results were noted among the medical students of Ethiopia, Pakistan, Angola, and Egypt [ 6 , 12 , 24 , 27 , 33 ]. Studies conducted in Saudi Arabia in the cities of Makkah and Taif reported that 63.0 and 80% of medical students, respectively, identified that refraining from breastfeeding may increase the incidence of BC [ 11 , 13 ].…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…The data showed that our students agreed that breastfeeding does not affect the incidence of BC. Similar results were noted among the medical students of Ethiopia, Pakistan, Angola, and Egypt [ 6 , 12 , 24 , 27 , 33 ]. Studies conducted in Saudi Arabia in the cities of Makkah and Taif reported that 63.0 and 80% of medical students, respectively, identified that refraining from breastfeeding may increase the incidence of BC [ 11 , 13 ].…”
Section: Discussionsupporting
confidence: 82%
“…On the other hand, other risk factors such as family history of BC are unmodifiable. Our study revealed insufficient knowledge among the responders regarding risk factors that are associated with BC, and family history was recognized by a fewer number of our students as a risk factor of BC compared with other studies [ 6 , 9 – 13 , 33 ].…”
Section: Discussioncontrasting
confidence: 81%
See 3 more Smart Citations